Lithuanian community of exiles in the West: return to a free Lithuania - Banionis, Juozas (Genocidas ir rezistencija, 2025)
The Second World War and the Soviet and Nazi occupations had a significant impact on the Lithuanian nation, leading to its division and dispersion. As the Second World War’s Eastern Front approached the Baltic countries, over sixty thousand Lithuanians made the decision to leave Lithuania for what they thought would be a temporary stay, until they could return to a homeland that was soon to be free again. They were not just war refugees, but became political exiles, eventually known as “dipukai”. The article highlights the formation of the Lithuanian war refugees in the DP camps into a single organisation, the Lithuanian Exiles’ Community (Lith. Lietuvos tremtinių bendruomenė, LTB). At the same time, it reveals the dedication of our people to preserve Lithuanian identity, maintain national solidarity and prepare for a free, independent Lithuania.
Keywords: war refugees; DP Lithuanians; dipukai; screening; LTB; Lithuanian Charter